The Expression of Tax and HBZ Genes in Serum-Derived Extracellular Vesicles From HTLV-1 Carriers Correlates to Proviral Load and Inflammatory Markers - de La-Roque, Debora Glenda Lima; Santos, Elaine Vieira; Rodrigues, Evandra Strazza; da Costa, Péricles Natan Mendes; Brauer, Verônica Soares; Almeida, Fausto; de Haes, Tissiana Marques; Takayanagui, Osvaldo Massaiti; Covas, Dimas Tadeu; Kashima, Simone (Frontiers in Microbiology, 2022)
Human T-lymphotropic virus 1 (HTLV-1) is the etiologic agent of adult cell leukemia/lymphoma (ATL) and HTLV-1 associated myelopathy/tropical spastic paraparesis (HAM/TSP). One of the major questions in HTLV-1 studies is related to the understanding of causes that lead to different clinical manifestations. However, it is well known that the viral genes tax and HTLV-1 basic leucine zipper factor (HBZ) are related to viral infectivity and the development of neurological and hematological diseases. Currently, there is evidence that HTLV-1 infected cells can release small extracellular vesicles (sEVs) involved in the mechanisms of viral particles spreading. Therefore, we evaluated the expression levels of tax and HBZ viral transcripts in serum-derived sEVs from HTLV-1 carriers, as well as the role of these vesicles in the modulation of the immune response. Three HAM/TSP carriers presented detectable levels of tax and HBZ transcripts in sEVs and were positively correlated to the proviral load (PVL) in peripheral blood mononuclear cells (PBMCs). The viral transcripts were only detectable in individuals with a PVL higher than 6,000/105 PBMCs. Additionally, it was observed that HBZ presented a 2–12-folds increase over tax expression units. Gene expression and secretory protein analysis indicated that PBMCs from blood donors and HTLV-1 carriers exposed to increasing doses of tax+ HBZ+ sEVs showed a dose-dependent increase in interferon (IFN)-γ and interleukin (IL)-8 transcripts and proteins. Interestingly, the increase in IL-8 levels was close to those seen in HTLV-1-infected PBMCs with high PVL. Taken together, these findings indicate that the expression of viral transcripts in serum-derived sEVs of HTLV-1 carriers is related to the PVL presented by the infected individual. Additionally, tax+ HBZ+ sEVs can induce the production of inflammatory cytokines in patients with low PVL, which may be related to the development of symptoms in HTLV-1 infection.